STRUCTURAL VECTOR AUTOREGRESSIVE UNTUK ANALISIS DAMPAK SHOCK NILAI TUKAR RUPIAH TERHADAP DOLAR AMERIKA SERIKAT PADA INDEKS HARGA SAHAM GABUNGAN - Annisa Rahmawati; Di Asih I Maruddani; Abdul Hoyyi (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2017)
Instability and depreciation of the rupiah be a motivating factor for investors to pull out a portfolio in Indonesia. The weakening of rupiah led to a decline in investor demand for stocks. Measurement of stock price fluctuations or portfolio using the Composite Stock Price Index (CSPI). The exchange rate and CSPI is a sensitive macroeconomic variables affected by shock and it takes restriction of macroeconomic structural model. Based on this, Structural Vector Autoregressive (SVAR) model is used. The purpose of this thesis is to analyze the impact of the exchange rate shock on CSPI through the description of Structural Impulse Response Function and Structural Variance Decomposition modeling based on a restriction on SVAR. SVAR also called the theoretical VAR used to respond to criticism on the VAR model where necessary the introduction of restrictions on economic models. By using daily data exchange rate of the rupiah against the US dollar and CSPI from January 2013 to December 2016 acquired the VAR model is stable and meets the white noise assumption as the basis for modeling residual SVAR and has a short-term restriction. The response of CSPI from the impact of the shock rupiah exchange rate is likely to experience an increase, while the response to the shock CSPI itself is fluctuating but tends to decrease. Patterns proportion shock effect on the exchange rate is increasingly rising stock index in the period of time, whereas the effect of the shock CSPI itself getting down on each period of time. Keywords : exchange rate, CSPI, SVAR, Structural Impulse Response Function, Structural Variance Decomposition